Structure and composition of the white grub complex (Coleoptera: Scarabaeidae) in agroecological systems of Northern Cauca, Colombia - Pardo Locarno, L.C.; Montoya Lerma, J.; Bellotti, Anthony C.; Schoonhoven, Aart van (Florida Entomological Society, 2005)
The larvae of some species of Scarabaeidae, known locally as chisas (whitegrubs), are important pests in agricultural areas of the Cauca, Colombia. They form a complex consisting of many species belonging to several genera that affect the roots of commercial crops. The objective of the present study was to identify the members of the complex present in two localities (Caldono and Buenos Aires) and collect basic information on their biology, economic importance, and larval morphology. The first of two types of sampling involved sampling adults in light traps installed weekly throughout one year. The second method involved larval collections in plots of cassava, pasture, coffee, and woodland. Each locality was visited once per month and 10 samples per plot were collected on each occasion, with each sample from a quadrants 1 m2 by 15 cm deep, during 1999-2000. Light traps collected 12,512 adults belonging to 45 species and 21 genera of Scarabaeidae within the subfamilies Dynastinae, Melolonthinae, and Rutelinae. Members of the subfamily Dynastinae predominated with 48% of the species (mostly Cyclocephala), followed in decreasing order by Melolonthinae (35%) and Rutelinae (15%, principally Anomala). Melolonthinae comprised 60% of the specimens (Plectris spp. 59.5% and Phyllophaga spp. 35.9%). A total of 10,261 larvae of 32 species was collected, including 12 species each of Melolonthinae (Phyllophaga, Plectris, Astaena, Macrodactylus, Ceraspis, Barybas, and Isonychus), Rutelinae (Anomala, Callistethus, Stigoderma, and Leucothyreus) and Dynastinae (principally Cyclocephala). At least a third of the species sampled as larvae are rhizophagous pests. Taken together, adult and larval sampling methods permitted a more precise definition of the whitegrub complex in Caldono and Buenos Aires.